Short time planning and allocation of cost saving in industrial microgrids - Derakhshandeh, S.Y.; Golshan, M.E.H.; Masoum, Mohammad Sherkat; Moghbel, Moayed (Institut Teknologi Sepuluh Nopember (ITS), 2012)
Industrial microgrids consist of many factories with distributed energy resources (DERs) and local electric loads that rely heavily on combined heat and power (CHP) systems. In this paper, a unit commitment (UC) for industrial microgrids is formulated to minimize the cost of generating electricity and heat via CHP systems and boilers. As each DER and boiler may have an individual owner, an approach is also presented to fairly allocate the cost saving among factories participating in the generation process. The proposed methods are implemented in an industrial microgrid consisting of 12 factories divided into three groups according to their levels of participations in the energy generation. Simulation results are analyzed to show the effectiveness of the proposed approaches.